Alimentary habits of futsal players from Paraná and Rio Grande do Sul states - Rodrigo Flores Sartori; Maria Eloiza Fiorese Prates; Vera Lucia Garcia Cardoso Tramonte (Journal of Physical Education (Maringá), 2008)
This study aimed at investigating the alimentary habits of futsal players from Paraná (PR) and Rio Grande do Sul (RS) states. Twenty-two athletes from two teams were evaluated. The 24 hours alimentary recordation method was used for data collection, as well as five additional questions. The data were analyzed by NUT program. The Primer program was used for the statistical analysis. The results showed that the magnesium, A vitamin, calcium and calorie components presented percentages below the daily recommendations (RDA). On the other hand, the components: protein, iron, C vitamin, sodium, presented high results, specially sodium. When the percentage averages of RDA adequacy between the two teams were compared, only the A vitamin presented significant statistical differences. In spite of showing the importance of an adjusted diet for the athlete 's performance, we can conclude that there seem not to be a concern of the team for a nutritional orientation.